In Spite of Everything, to Appear - Chávez Mac Gregor, Helena (Re-visiones, 2024)
This article examines the notion of appearance in the context of the violence and terror exemplified by the mass disappearance of 43 students from the Raúl Isidro Burgos Rural Teacher-Training College. This case will help to explore the conditions of politics in zones where the state has transformed itself into a war machine and the practices in which, in spite of all, the common can be made to appear. Revisiting a project of the Teatro Ojo collective, What is to come, the paper articulates approaches of Hannah Arendt, Georges Didi-Huberman and Jacques Rancière to think of the notion of appearance as an aesthetic operation that is also political.